PENGEMBANGAN INSTRUMEN TES PADA MATERI EKOSISTEM KELAS X SMA/MA - Indah Putri Agustina; Fitra Suzanti; Mariani Natalina L (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The test instrument is a measuring tool in the form of a number of questions that require answers to measure a person's level of ability. The purpose of this research is to produce a valid test instrument on ecosystem material in class X SMA/MA. This research was conducted at the Biology Education Campus, FKIP Riau University and SMAN 1 Pekanbaru. This type of research is development research using the ADDIE model, which consists of the Analysis, Design, and Development stages. The data collection instrument used was a validation sheet. The validation sheet consists of 3 aspects, namely material aspects, construction aspects, and language aspects. The three aspects include material aspects with an average of 3.95 very valid category, construction aspects with an average of 3.70 very valid category, language aspects with an average of 3.91 very valid category. The aspect that received the highest score was the material aspect with an average score of 3.95 with a very valid category. Based on the results of the study, it can be concluded that the test instrument on the ecosystem material for class X SMA/MA that has been developed is included in the very valid category in all aspects with an average validity value of 3.85, so that the test instrument that has been developed can be used in learning biology.Key Word: Test Instrument, Ecosystem.